Transformational contribution of technology to studio culture: experience of an online first-year architecture design studio during the COVID-19 pandemic - Hassanpour, Badiossadat (Emerald Group Publishing Ltd, 2023)
Purpose - Design studios experienced an unprecedented contribution of technology when it came to organizing studios online, as imposed by COVID-19, which requires exploration of its impacts on the main metaphors of education, learning dimensions, and undoubtedly studio culture. Design/methodology/approach - In order to explore the impacts on the key dimensions of learning, a careful investigation was carried out from organizational, instructional, and learner points of view. The investigation utilized thematic analysis of records of pedagogical actions, as well as online communications, performance, and questionnaire responses of students to infer the conclusions. The freshmen architecture students were found to be an important group for study since they had no previous experiences in on-site design studios and will continue their education based on their first-year experiences. Findings -Exploration of indicators including reflective dialogue, retention, transfer of learned information to decisions, processing feedback as an investment in future performance, and self-regulation-as major contributors to design learning revealed that first-year students exhibited strong presence and interaction during online studio, and students' individuality influenced the teaching environment in terms of content and process. Hence, sense of belonging, which is a revamped feature of authentic context and studio culture, expands toward fortification of bottom-up educational frontiers. Originality/value - Developing pedagogies with no concern for the unprecedented impacts of the transformative role of technology on fundamental layers of design education will adversely influence students' chances of personal and professional success. The findings in this paper, regarding the transformational impacts of technology on design studio culture, follow investigation of the direction it has led current and can lead future design education. The study provides unique support for crystalizing new teaching and learning opportunities and pedagogical developments.
Keywords: Technology; Studio culture; Architectural education; Online studio; First year